PENGARUH PENDIDIKAN DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEMUDA DAN OLAHRAGA ACEH - Fitriliana Fitriliana; Putri Mauliza; Filia Hanum; Juwita Juwita (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the magnitude of the effect of education and job training on employee performance at Pemuda dan Olahraga Aceh’s government. This research is a quantitative research. The sample of this research is the employees of the Aceh’s government. Data was collected using questionnaires, interviews, documentation and observation. Questionnaires were used to measure the variables of education and job training as well as employee performance, while interviews, documentation and observations were used to support research data. The results showed that education and job training had a positive and significant influence on employee performance and the effect was in the moderate category as indicated by the regression equation Y = 0.305 + 0.278 with a regression coefficient (β) of 1.822, a coefficient of determination (R²) of 0.345 and obtained tcount of 2.650 is greater than ttable (2.650>1.993). Based on the coefficient of determination (R²) 0.345, it means that 34.5% of employee performance is influenced by education and job training of employees while the remaining 65.5% is influenced by other variables not examined in this study.